Legal Analysis of Environmental Criminal Acts: Tailings Waste Disposal by PT. Freeport Indonesia in Mimika Regency - Kogoya, Delson; Renggong, Ruslan; Halwan, Muh. (Indonesian Journal Of Law Studies, 2024)
This study aims to determine the enforcement of environmental criminal law and the legal responsibility of PT. Freeport Indonesia for the disposal of tailings waste in Mimika Regency. This research method is normative-empirical using primary data and secondary data. Primary data was obtained through interviews with related parties, namely the Mimika Resort Police, the Mimika Regency Environmental Service and Environmental Care Organizations. The results of the study indicate that the enforcement of environmental criminal law due to tailings waste pollution by PT. Freeport Indonesia has not been able to be implemented effectively. This is because the process of proving and determining the causal relationship between the act of pollution and the victim requires special experts and laboratories and the enforcement of environmental criminal law still relies on administrative sanctions. The application of criminal sanctions is still the ultimum remedium which is the last resort in its application. The legal responsibility of PT. Freeport Indonesia due to the disposal of tailings waste must be carried out in accordance with the provisions of laws and regulations as stipulated in Law Number 4 of 2009 concerning Minerals and Coal and Law Number 32 of 2009 concerning Environmental Protection and Management, regarding compensation for losses due to tailings waste pollution.